Prove

Asked by Sejal Gupta | 16th Sep, 2010, 05:18: PM

Expert Answer:

L.H.S =( cosx +cosy) +( cosz + cos(x+y+z))           = 2cosx+y2cosx-y2 + 2 cosx+y+2z2cosx+y2                        [   using the formula cosC + cosD = 2cosC+D2cosC-D2                                       and cos(-θ) = cos θ]          = 2cosx+y2cosx-y2+cosx+y+2z2         =2 cosx+y22cosx+z2cosy+z2        using above result again.        = 4cosx+y2cosy+z2cosx+z2        =R.H.S">

Answered by  | 17th Sep, 2010, 10:12: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.